Feasability of yeast and bacteria identification using UV-VIS-SWNIR difusive reflectance spectroscopy - Silva, João S. (2008)
UV-VIS spectroscopy is a powerfull qualitative and quantitative technique used in analytical chemistry, which gives information about electronic transitions of electrons in molecular orbitals. As in UV-VIS spectra there is no direct information on characteristic organic groups, vibrational spectroscopy (e.g. infrared) has been preferred for biological applications. In this research, we try to use state-of-the-art fiber optics probes to obtain UV-VIS-SWNIR diffusive reflectance measurements of yeasts and bacteria colonies on plate count agar in the region of 200-1200nm; in order to discriminate the following microorganisms: i) yeasts: Saccharomyces cerevisiae, Saccharomyces bayanus, Candida albicans, Yarrowia lipolytica; and ii) bacteria: Micrococcus luteus, Pseudomonas fluorescens, Escherichia coli, Bacillus cereus. Spectroscopy results show that UV-VIS-SWNIR has great potential for identifying microorganisms on plate count agar. Scattering artifacts of both colonies and plate count agar can be significantly removed using a robust mean scattering algorithm, allowing also better discriminations between the scores obtained by singular value decomposition. Hierarchical clustering analysis of UV-VIS and VIS-SWNIR decomposed spectral scores lead to the conclusion that the use of VIS-SWNIR light source produces higher discrimination ratios for all the studied microorganisms, presenting great potential for developing biotechnology applications.